Death at the opposite ends of Eurasian continent : Mortality trends in Taiwan and the Netherlands. - Engelen, Th. (Theo) (Life at the Extremes, 4., 2011)
Historical demographers since Malthus have characterized the West-European and Chinese demographic regimes as systems under low and high pressure, respectively. This volume examines the operation of the positive check at the two ends of the Eurasian continent by taking the Netherlands and Taiwan as representatives of the West-European and Chinese mortality regimes. Are these cases as different as the low and high pressure contrast implies? The volume opens with a cluster of chapters dealing with long term trends in mortality and the accompanying changes in causes of death (Chapters 1 through 4.